Proposed improvements in the teaching of social studies in the Bataan High School - Talastas, Florencia Manuel 1948- (1977)
This paper aimed to improve the teaching of social studies at the Bataan High School (BHS). Interviews, observations of social studies classes, documentary analysis of lesson plans used by the teachers of social studies, and questionnaires were the methods employed. The researcher found out that social studies teachers in the school are not well-informed of the trends and innovations in the new social studies. Teachers rely on the use of only one textbook and one pamphlet, with the objectives stated in non-behavioral terms. Lecture method with recitation is the most commonly used technique and the norm-referenced test, or pencil-paper test is employed as the only evaluating technique to measure students' achievement. Aware of these problems, the researcher gave recommendations directed to social studies teachers, writers of instructional materials, school administrators, and the Department of Education.